1965
DOI: 10.1161/01.res.17.5.394
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Blood Flow in the Dog

Abstract: That the radiorubidium distribution method provides good estimates of blood flow to the gastrointestinal organs was demonstrated by comparing the arterial concentration course of the isotope with the simultaneous venous concentration for the individual organs. Blood flow to stomach, intestine and colon are accurately assessed by this method. Estimates for pancreas, gall bladder, esophagus and duodenum are probably correct. Average perfusion rates in the pentobarbital anesthetized dog are, in cc/min.g of tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1
1

Year Published

1971
1971
1988
1988

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 5 publications
5
22
1
1
Order By: Relevance
“…It may be that the duodenum is functionally different from the jejunum. However, we should note that duodenal and jejunal blood flows are comparable (Delaney & Custer, 1965). Our own work also indicates that resting heat production is similar in the two regions (Durotoye & Grayson, 1971).…”
Section: Discussionsupporting
confidence: 49%
“…It may be that the duodenum is functionally different from the jejunum. However, we should note that duodenal and jejunal blood flows are comparable (Delaney & Custer, 1965). Our own work also indicates that resting heat production is similar in the two regions (Durotoye & Grayson, 1971).…”
Section: Discussionsupporting
confidence: 49%
“…The rela tively good agreement between calculated and determined (table 2) values for bile acid concentration in portal blood suggests the same relative blood flow reported previously [6,9], The present study shows that the distal small intestine was by far the major site of bile acid absorption tunneling as much as 73.8% of total bile acid during enterohepatic circulation. Bile acid absorption from the large intestine constituted only 9.4%.…”
Section: Discussionsupporting
confidence: 90%
“…In dog, the small intestinal blood flow was about four times larger than that of the large intestine [6], It was also reported that the proximal and distal small and large intes tines receive a blood flow per gram tissue approximately in the same order [6,9]. As shown in table 3, the mean total bile acid concentration is 49.8 nmol/ml in the proxi mal small intestine, 219.5 nmol/ml in the distal small intestine, 50.1 nmol/ml in the proximal large intestine and 61.8 nmol/ml in the distal large intestine.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…5DANIhLE AUGIER AND OTHERS Jones, 1960;Delaney & Custer, 1965). However, it is not known whether these alterations are actually involved in the regulation of the secretary process.…”
Section: Introductionmentioning
confidence: 99%